The Improving Young Learners’ Vocabulary Trough TPR (Total Physical Response) With Song - Bellaneta Amalin Kuntadirga (English Education Program, Education Faculty, Universitas Nurul Huda, 2023)
The research was based on a preliminary study on the causes of problems related to the students’ inability to memorize vocabulary in English. This research was aimed at finding out the effectiveness of using the TPR (Total Physical Response) with song to improve vocabulary mastery of 3rd grade students at SDN Darsono 04 Jember in the academic year 2022/2023. The researcher designing the lesson plans, implementing the actions, making observations and reflecting on the results. The subjects of this research study were 3rd grader students from SDN Darsono 04 Jember in the academic year 2022/2023. This research was conducted in two cycles following the procedures for action research, namely planning, implementing, observing and reflecting. To collect data, the researcher used instruments of observation and test. The data obtained were presented quantitatively. The findings showed that TPR with song method were effective in improving students' vocabulary. This can be seen in the improvements after each cycle. Prior to the research, only one of the students scored above the KKM. In the first cycle, 3 out of 8 students who entered scored above the KKM. Whereas in the second cycle, 8 out of 8 students scored above the KKM. This means that the students responded positively to the implementation of this method.